Tidal and storm surges sea level at cape Yam-Sale (the gulg of Ob) - G. N. Voinov; A. A. Piskun; Г. Н. Войнов; А. А. Пискун (Государственный научный центр Российской Федерации Арктический и антарктический научно-исследовательский институт, 2016)
Average estimates of the harmonic constants of tides are given over the summer period (July–September) at Cape Yam-Sale (Obskaya Guba), obtained using least-squares method version of the AARI over the period from 1937 to 1960. According to the residual series (observation minus prediction) are produced a study of the wind-surges of sea level ﬂ uctuations in some years during the summer period 1937–1960. Verify the predictive equations V.G. Kort and N.A. Labzovskiy is considered to calculate the storm surges. Приведены средние оценки гармонических постоянных приливов за летний период (июль–сентябрь) у мыса Ям-Сале (Обская губа), полученные с помощью МНК за период с 1937 по 1960 г. По остаточным рядам (наблюдения минус предвычисления) произведено исследование сгонно-нагонных колебаний уровня моря в отдельные годы за летний период 1937–1960 гг. Выполнена проверка прогностических уравнений В.Г. Корта и Н.А. Лабзовского для расчета сгонно-нагонных колебаний.